Copper mediates life history responses of Daphnia pulex to predation threat - Becker, Dörthe; Beckerman, Andrew P. (Frontiers in Ecology and Evolution, 2022)
A key challenge for ecological and ecotoxicological risk assessment is to predict the risk of organisms when exposed simultaneously to multiple stressors in sub-lethal concentrations. Here, we assessed whether sub-lethal concentrations of an anthropogenic stressors, the heavy metal copper (Cu), mediates the impacts of a natural ecological threat to species, predation risk, among six distinct Daphnia pulex clones. We investigated the interaction between the two stressors on morphological defences and on several life-history traits including maturation time, size at maturity somatic growth rate and survival rates. Combining a life table experiment on a response surface design, we found no evidence that the heavy metal copper mediates the effects of predator cue induced morphological responses in the tested Daphnia pulex clones. However, our data indicate that copper can mediate several key life-history responses to predation risk. For age at maturity, we found also clear evidence that the observed interaction between predation risk and copper varied by whether clones were strong or weak morphological responders. Specific exploration of the relationship between morphological responses and life history traits under predation risk and copper suggest a strong hypothesis for multiple strategies to deal with multiple stressors. While interactions between different stressors make it harder to predict their outcomes, and ultimately assess water quality regulations about the effects of such stressors, our study provides evidence that life history theory can aid in understanding and predicting their impacts.